1984
DOI: 10.1159/000233531
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Effector-Suppressor T Cells by an Antigen-Specific Suppressor T Cell Factor and Lyt-1<sup>+</sup>,2<sup>+</sup>,3<sup>+</sup> T Cells

Abstract: The cellular consequences in the suppression of IgG antibody formation initiated by an antigen-specific suppressor T cell factor (TsF) were investigated. The initial step of the suppression is the production of TsF by Lyt-2+,3+ T cells (Tsi) which activates Lyt-1+,2+,3+ acceptor T cells in the nylon wool-adherent T cell population. The activated Lyt-1+,2+,3+ T cells further generate a new effector-suppressor T cell (Tse) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Thus, once Id+ I-J" Ts cells are acti vated, they could act on anti-idiotypic T cells or I-J recognizing T cells. Our previous study [4] determined the I-J-restricted 'transduction' process, while in this report we extended our observation to the anti-idiotypic Lyt-l+2+3+ 'transducer' T cells. This Id-restricted pathways should parallel with the carrier-specific 'transduction' by TsF with I-J restriction in the gene ration of final suppressor effector.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Thus, once Id+ I-J" Ts cells are acti vated, they could act on anti-idiotypic T cells or I-J recognizing T cells. Our previous study [4] determined the I-J-restricted 'transduction' process, while in this report we extended our observation to the anti-idiotypic Lyt-l+2+3+ 'transducer' T cells. This Id-restricted pathways should parallel with the carrier-specific 'transduction' by TsF with I-J restriction in the gene ration of final suppressor effector.…”
Section: Discussionsupporting
confidence: 57%
“…The majority of the response suppressed by TsF was NPb idiotype positive. This allotype-res tricted suppression gives a clear distinction from the previously reported pathway of the carrier-specific suppression in that TsF was capable of suppressing the responses mounted only by I-J compatible spleen cells regardless of the Igh-allotype [24], Carrier-spe cific TsF was found to activate an intermediary T cell of Lyt-T2+3+ phenotype to 'transduce' the final effec tor suppressor T cells only when TsF and transducer T cells share the same I-J but not Igh genotypes [4], The present study indicates that the IgVH-restricted suppression of NPb idiotype also requires the pres ence of an Lyt-1+2+3+ 'transducer'T cells to convey the effect of NPb-TsF. Such transducer cells are naturally present in strains with Ighb allotype regardless of their H-2 haplotypes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The absorption studies with immunoadsorbents of antigen and antibodies revealed that the intact TaF is a heterodimer of two discrete polypeptide chains, one carrying a determinant detectable by a monoclonal anti-Tindd directed to an Igh-1-linked allotypic structure of T cells and being associated with the antigen-binding site and the other expressing a unique determinant controlled by the I-A subregion of murine H-2 major histocompatibility complex but being different from known class II polypeptide chains. The antigen-binding polypeptide has an isoelectric point of pH 5.6, and the I-A polypeptide has an isoelectric point of pH 6.3. Two types of antigen-specific T-cell factors, one able to suppress (TsF) and the other able to augment (TaF) the antibody response, have been reported from our laboratory (1)(2)(3). These factors share certain interesting immunological characteristics and are considered to play important roles in the regulation of the immune response (reviewed in ref.…”
mentioning
confidence: 99%